2015
DOI: 10.1002/jhet.2414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Evaluation of Some Nicotinonitriles

Abstract: in Wiley Online Library (wileyonlinelibrary.com).One-pot condensation of malononitrile 1, furan-2-carbaldehyde 2, butan-2-one 3, and ammonium acetate in ethanol, followed by cyanoacetylation of the formed nicotinonitrile 4 with 3-(3,5-dimethyl-1H-pyrazol-1yl)-3-oxopropanenitrile 5 afforded the cyanoacetamide 6. Compound 6 was used as a key intermediate for synthesis of nicotinonitriles via reaction with different reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
(21 reference statements)
0
34
0
Order By: Relevance
“…The synthetic strategies adopted to obtain the corresponding N ‐2‐amino‐4‐(furan‐2‐yl)‐5,6‐dimethylnicotinonitrile are depicted in Schemes . The starting material, 2‐amino‐4‐(furan‐2‐yl)‐5,6‐dimethylnicotinonitrile ( 4 ) was prepared, was obtained via one‐pot condensation of malononitrile ( 1 ), furan‐2‐carbaldehyde ( 2 ), butan‐2‐one ( 3 ), and ammonium acetate in ethanol, as previously described (Scheme ). Further, refluxing of compound 4 with benzoylisothiocynate ( 5 ) in 1,4‐dioxan gave N ‐thiouredopyridine derivative 6 , which transformed to pyridine[2,3‐d] pyrimidine derivative 8 upon heating with ethylchloroacetate 7 in ethanol in the presence of sodium ethoxide (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic strategies adopted to obtain the corresponding N ‐2‐amino‐4‐(furan‐2‐yl)‐5,6‐dimethylnicotinonitrile are depicted in Schemes . The starting material, 2‐amino‐4‐(furan‐2‐yl)‐5,6‐dimethylnicotinonitrile ( 4 ) was prepared, was obtained via one‐pot condensation of malononitrile ( 1 ), furan‐2‐carbaldehyde ( 2 ), butan‐2‐one ( 3 ), and ammonium acetate in ethanol, as previously described (Scheme ). Further, refluxing of compound 4 with benzoylisothiocynate ( 5 ) in 1,4‐dioxan gave N ‐thiouredopyridine derivative 6 , which transformed to pyridine[2,3‐d] pyrimidine derivative 8 upon heating with ethylchloroacetate 7 in ethanol in the presence of sodium ethoxide (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…An example of a one‐pot synthesis is the 2‐amino‐4‐(substituted) nicotinonitrile . In view of these facts and as a continuation of our research program on the chemistry of nicotinonitrile and furan , the present investigation aimed to synthesize and characterize newer nicotinonitrile incorporating furan moiety. It was found that 2‐amino‐4‐(furan‐2‐yl)‐5,6‐dimethylnicotinonitrile (4 ) is an excellent building block for the synthesis of the target objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Thiazole and pyrazole derivatives were synthesize by Gouda et al . utilizing 4,5,6,7‐tetrahydrobenzothiophene moiety as a base. Derivatives were assessed for in vitro antimicrobial activity using Ampicillin as standard.…”
Section: Introductionmentioning
confidence: 99%
“…) or pyrazole (Fig. ) moieties brought about remarkable activity against B. theringiensis , K. pneumoniae , Botrytis fabae , and Fusarium oxysporum .…”
Section: Introductionmentioning
confidence: 99%
“…In view of all these facts and as a continuation of our work on the synthesis of new heterocyclic derivatives, the present review presents a systematic and comprehensive survey of the method of preparation, reactivity, and the anticancer, antitumor, and antimicrobial activities of nicotinonitriles and their derivatives.…”
Section: Introductionmentioning
confidence: 99%